Rules versus Empathy: When Primary School Admission Age Requirements Meet the Child-Friendly School Approach - Liesma Zalianty (State Islamic University of Sultan Syarif Kasim Riau, 2024)
The minimum age requirement for primary school admission constitutes one of the administrative criteria within the student admission policy, aiming to ensure regulatory certainty while supporting children's readiness to participate in formal education. Nevertheless, the implementation of this policy is frequently perceived as insufficiently accommodating the diversity of children's developmental readiness, as advocated by the principles of the Child-Friendly School (CFS) approach. This study aims to examine the relationship between the minimum age requirement for primary school admission and the principles of Child-Friendly Schools, while identifying areas of convergence as well as potential tensions between the two. The study employed a qualitative library research design. Data were collected from peer-reviewed journal articles, educational regulations, and other relevant scholarly literature, and subsequently analyzed using qualitative content analysis through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the age requirement primarily functions as an administrative mechanism to ensure consistency and certainty in the student admission process. However, school readiness is inherently multidimensional, encompassing cognitive, linguistic, socio-emotional, and self-regulation competencies, and therefore cannot be adequately assessed solely on the basis of chronological age. From the perspective of the Child-Friendly School framework, student admission policies should prioritize the best interests of the child by incorporating more comprehensive school readiness assessments. Consequently, harmonizing age-based admission regulations with holistic school readiness assessment represents a crucial strategy for establishing a fair, inclusive, and child-centered admission system that accommodates the developmental needs of every child.